Drug survival and reasons for discontinuation of the first biological disease modifying antirheumatic drugs in Thai patients with rheumatoid arthritis: Analysis from the Thai Rheumatic Disease Prior Authorization registry - Pongthorn Narongroeknawin (2018)
© 2016 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd Aim: To evaluate and compare the retention rate of biological disease-modifying antirheumatic drugs (bDMARDs) in real-life practice and identify risk factors related to remission and drug discontinuation in patients with rheumatoid arthritis (RA). Method: A total of 256 patients fulfilling criteria for RA and starting bDMARD between December 2009 and October 2014 were selected from the Rheumatic Disease Prior Authorization registry. Baseline demographic and clinical data were recorded. The cumulative probability of bDMARD discontinuation over 5 years of follow-up and factors associated with RA remission and bDMARD withdrawal were analyzed. Results: Almost half (46%) of patients were initially treated with rituximab (RTX), with 33% treated with etanercept (ETN) and 21% with infliximab (IFX). Fewer than 10% were subsequently switched to a second bDMARD. The 1- and 5-year remission rates in patients continuing their first bDMARD were 7.2% and 21.5%, respectively. At 5 years, the drug survival rates for RTX, ETN and IFX were 50%, 25% and 22%, respectively. Multivariate analysis showed that RTX was significantly associated with highest drug survival. Relative to RTX, the hazard ratios for discontinuation of IFX and ETN were 2.60 (95% confidence interval [CI] 1.53–4.42) and 2.15 (95% CI 1.36–3.42), respectively. Thirty-nine percent of patients stopped treatments, due to inadequate response (42%), serious adverse events (22%), nonadherence (14%) or remission/low disease activity (13%). Conclusion: Over 5 years, only one-third of patients continued using their first bDMARD. The leading cause of drug discontinuation was inadequate response.